The The Effectiveness of Learning Pronunciation Through English Content by English With Lucy on YouTube - Putri Andini; Zaitun Zaitun (Jurnal Studi Guru dan Pembelajaran, 2022)
Pronunciation is fundamental and includes what anyone who wants to communicate or is in the process of communicating learning English should understand. One way to practice pronunciation is to use YouTube. YouTube is a good audiovisual combination for pronunciation practice because it not only shows recordings or videos, but also provides sound. One of the content creators who explained the pronunciation material was a YouTuber running the English With Lucy channel. This study uses a qualitative method. The study specifically targeted high school students who studied remotely online to practice their pronunciation skills. In collecting the data, this study used several tools: testing and observation. This results of data analysis is in form statements responden. Learning English pronunciation requires hands-on work with the right model, such as a native speaker. So, using YouTube training videos with native speakers as a resource, you can learn English pronunciation very easily.